Procesamiento De Datos Usando Scraping Y Etl Para Realizar Recomendaciones Personalizadas Sobre Productos De Tecnología (2023)
Ádalo Tech, a company that markets hardware and software products, currently has a line of business called URU that offers customers a guided search for the product they want based on a form in which they must answer a series of questions. Notwithstanding the above, the Internal measurements carried out by the company show that this process can take clients several hours, a problem that is accentuated by the variability in the catalog of products and services.